Association between red cell distribution width–and–albumin ratio and the risk of peripheral artery disease in patients with diabetes - Li, Dongling; Long, Juan; Zhang, Jialu; He, Meinan; Zeng, Qingxiang; He, Qiaoling; Zhan, Wanhua; Chi, Yongqian; Zou, Mengchen (Frontiers in Endocrinology, 2024)
Aim: To explore the association between red blood cell distribution width/albumin ratio (RAR) and the risk of peripheral artery disease (PAD) in patients with diabetes.: This cross-sectional study extracted the data of 1125 participants with diabetes from the National Health and Nutrition Examination Survey (NHANES) database. A weighted univariable logistic regression model was used to explore variables associated with PAD. With PAD as the outcome variable, a weighted logistic regression model was established. The odds ratio (OR) and 95% confidence interval (CI) were effect size.Results: After adjusting for covariates, the risk of PAD in patients with diabetes was observed in those with higher RAR (OR=1.83, 95%CI: 1.06-3.15). Also, RAR ≥3.25 was related to increased risk of PAD in patients with diabetes (OR=2.04, 95%CI:1.05-3.95). In people with diabetes aged ≥65, RAR was a risk factor for PAD with an OR value of (OR=2.67, 95%CI: 1.30-5.46). RAR ≥3.25 was associated with increased risk of PAD (OR=3.06, 95%CI: 1.15-8.11) relative to RAR<2.80. In diabetes people who smoked, the risk of PAD was elevated in those with RAR ≥3.25 (OR=2.85, 95%CI: 1.28-6.32). As for patients with CVD, the risk of PAD was elevated as the increase of RAR (OR=2.31, 95%CI: 1.05-5.10). RAR ≥3.25 was correlated with increased risk of PAD (OR=3.75, 95%CI: 1.42-9.87). The area under the curve (AUC) of RAR for the risk of PAD in patients with diabetes was 0.631 (95%CI: 0.588-0.675).Higher RAR was related to increased risk of PAD in patients with diabetes. The findings might offer a reference for the management of PAD in patients with diabetes.